Design with the Desert Conservation and Sustainable Development - Malloy, Richard; Brock, John; Floyd, Anthony; Livingston, Margaret; Webb, Robert H. (Taylor & Francis, 2013)
The modern southwestern cities of Phoenix, Tucson, Las Vegas, Albuquerque, and El Paso occupy lands that once supported rich desert ecosystems. Typical development activities often resulted in scraping these desert lands of an ancient living landscape, to be replaced with one that is human-made and dependent on a large consumption of energy and natural resources. Design with the Desert: Conservation and Sustainable Development explores the natural and built environment of the American Southwest and introduces development tools for shaping the future of the region in a more sustainable way. Explore the Desert Landscape and Ecology This transdisciplinary collaboration draws on insights from leading authorities in their fields, spanning science, ecology, planning, landscape development, architecture, and urban design. Organized into five parts, the book begins by introducing the physical aspects of the desert realm: the land, geology, water, and climate. The second part deals with the "living" and ecological aspects, from plants and animals to ecosystems. The third part, on planning in the desert, covers the ecological and social issues surrounding water, natural resource planning, and community development. Bring the Desert into the City The fourth part looks at how to bring nature into the built environment through the use of native plants, the creation of habitats for nature in urban settings, and the design of buildings, communities, and projects that create life. The final part of the book focuses on urban sustainability and how to design urban systems that provide a secure future for community development. Topics include water security, sustainable building practices, and bold architecture and community designs. Design Solutions That Work with the Local Environment This book will inspire discussion and contemplation for anyone interested in desert development, from developers and environmentalists to planners, community leaders, and those who live in desert regions. Throughout this volume, the contributors present solutions to help promote ecological balance between nature and the built environment in the American Southwest-and offer valuable insights for other ecologically fragile regions around the world.